(untitled) (World Bulletin of Public Health, 2026)
Recurrent pregnancy loss (RPL) is a multifactorial reproductive disorder characterized by repeated pregnancy failure and persistent diagnostic uncertainty. This review summarizes current evidence on the clinical definition and major etiopathogenetic mechanisms of RPL, including chromosomal abnormalities, antiphospholipid syndrome, immune dysfunction, endocrine-metabolic disturbances, and uterine structural abnormalities. The strongest evidence supports embryonic chromosomal errors and antiphospholipid syndrome as major contributors, whereas the roles of inherited thrombophilia, natural killer cells, and some metabolic markers remain less consistent. Overall, RPL requires a multidisciplinary, evidence-based, and patient-centered approach, although a considerable proportion of cases remain unexplained.